Alternative models to finance irrigation services and their impacts along the rice chain value : a case study in Central Thailand - Peerasut Saringkarn; Jourdain, Damien; Perret, Sylvain Roger; Babel, Mukand Singh; Clemente, Roberto S.; Thailand (HM King) (Pathum Thani : Asian Institute of Technology, 2012)
This study focused on the assessment of value of irrigation water used in paddy field and cost of irrigation water services in Sam Chuk O&M project, Suphan Buri province, Central part of Thailand. Specifically, the study involves primary and secondary data collection from the study site related to production cost of rice farmers, yield of rice production, climates, soil type, crop calendar, and the rice marketing channelsystem of Suphan Buri province. The amount of irrigation water applied in paddy field was used CROPWAT 8.0 model in estimation then used this amount to calculate the value of irrigation water using the Residual Imputation Method (RIM). Results show that the average value of irrigation water had contributed into 2 cases. For case without government subsidy, the value of irrigation water is 0.017 US$/m3and 0.019 US$/m3for dry and wet season, respectively. For case with government subsidy, the value of irrigation water is 0.033US$/m3and 0.045US$/m3for dry and wet season, respectively.In addition,thecost of irrigation project was based on Sam Chuk O&M project investment. Results show that the average cost of irrigation water service per area is 140.95 US$/ha/year or in form the mass unit of paddy production is 13.063 US$/ton and 13.477 US$/ton for dry and wet season, respectively.Moreover, theadded value of paddy production is consideredat the primary milling process that consistedbrown rice bran, husk, white rice bran and broken white rice.In addition, milling process of white rice 1 ton had usedthe material production or paddy 2 tons. Therefore, the added value of by-productfrom milling process is 138.433 US$/ton. Moreover, the total paddy production for each season is around 50% that is 940,000 tons and 950,000 tons for dry and wet season, respectively. Therefore, 90% of white rice production in Suphan Buri province is selling to export market and another 10% is selling to domestic market.In concludethe new finance irrigation serviceto cover irrigation water service and maintenance costs is provided by 4 scenarios from the output that mention above. This is only scenario of sharing cost of irrigation water service. In addition, there are needssupporting from the related institutional offices
A thesis submittedin partial fulfillment of the requirements for the degree of Master of Engineering inWater Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2012
Keywords: Irrigation water -- Cost control -- Thailand, Central; Irrigation water -- Thailand, Central; Rice -- Irrigation -- Thailand, Central